CHLORELLA VULGARIS MODULATES HYDROGEN PEROXIDE-INDUCED DNA DAMAGE AND TELOMERE SHORTENING OF HUMAN FIBROBLASTS DERIVED FROM DIFFERENT AGED INDIVIDUALS - Makpol, Suzana; Yaacob, Nadia; Zainuddin, Azalina; Yusof, Yasmin Anum Mohd; Wan Ngah, Wan Zurinah (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The objective of this study was to investigate the modulatory effect of Chlorella vulgaris on cultured fibroblast cells derived from young and old aged individuals focusing on DNA damage, telomere length and telomerase activity. Dose-response test of the algal extract on cells in both age groups revealed that optimum viability was observed at a concentration of 50 Î¼g/ml. Results obtained showed that Chlorella vulgaris exhibited protective effects against H2O2-induced oxidative stress as shown by the reduction in damaged DNA caused by H2O2 treatment (p<0.05) in Chlorella vulgaris pre- and post-treated groups (p<0.05). Pre-treatment of Chlorella vulgaris resulted in a significant decrease in DNA damage suggesting a bioprotective effect against free radical attacks. A decline in DNA damage was observed in post-treated cells which proves Chlorella vulgaris to present bioremediative properties. In cells induced with oxidative stress, telomere length decreased significantly coupled with a concomitant decline of telomerase activity (p<0.05). However, these reductions were prevented with prior and post treatment of Chlorella vulgaris. Therefore, we concluded that Chlorella vulgaris exhibited bioprotective effects especially in cells obtained from young donor but were more bioremediative for cells obtained from old donor as indicated by DNA damage, telomere shortening and reduction in telomerase activity.